Development of Risk Management Model for Creative Industry: A Cross-Industry Quantitative and Comparative Approach - Prasetya, Luhur Adi; Mahardika, Arvendo; Rofiudin, Amir; Haq, Salsabila Thifal Nabil; Ichwanto, Muhammad Aris (Journal of Economics, Management, Accounting and Computer Applications, 2025)
Creative industries in Indonesia, including PT Kreasi Ngalam Media (AboutMalang.com), contribute significantly to GDP, but face challenges such as dependence on creative individuals, changing market trends, and global economic uncertainty. This research aims to develop a comprehensive risk management model through a survey of 45 respondents, semi-structured interviews, and cross-sector meta-analysis. The findings identified operational, reputational and financial risks, with technical glitches (score 4.2) and reliance on technology vendors (4.1) as the main operational issues. Negative reviews (4.4) were the biggest reputational risk, while dependency on key clients (4.0) stood out as the main financial risk. Suggested mitigation strategies include client diversification, implementation of recurring revenue models, investment in technology, and development of HR competencies. A cross-cutting analysis showed the importance of implementing predictive technology and strengthening infrastructure to enhance the firm's resilience. The developed model brings together operational, reputational, financial, and sustainability risk management, providing strategic guidance that can be applied by PT Kreasi Ngalam Media and other companies in the creative industry to improve competitiveness and business continuity.